Adoption of Cloud Accounting: Opportunities, Barriers, and Implications for SMEs - Qoriah, Desi (Indonesian Scientific Publication, 2025)
Cloud accounting has become a key innovation in financial management, improving efficiency, transparency, and sustainability. This narrative review synthesizes literature on its adoption and impact, with emphasis on business sustainability. Systematic searches were conducted in Scopus, Web of Science, and Google Scholar using targeted keywords on efficiency, transparency, SMEs, and financial performance. Only peer-reviewed, English-language studies directly addressing cloud accounting and sustainability were included. Findings show that cloud accounting reduces administrative workloads, enhances reporting accuracy, and promotes transparency through real-time data access. SMEs benefit most, gaining cost savings, better cash flow management, and operational flexibility. Yet adoption is hindered by security concerns, high initial costs, and limited infrastructure, particularly in developing countries. Integration with AI, blockchain, and big data further strengthens predictive capacity, accountability, and sustainability goals. Systemic factors such as robust digital infrastructure and supportive government policies are crucial in driving adoption. Overcoming barriers requires joint efforts by firms, governments, and technology providers to improve security, lower costs, and expand digital capacity. The review concludes that cloud accounting functions not only as a technological innovation but also as a strategic tool for sustainable business development. Future research should explore long-term financial and sustainability impacts, regional differences, and the governance role of cloud systems in fostering transparency and accountability.